2014
DOI: 10.1101/cshperspect.a016311
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Mediators in the Resolution of Inflammation

Abstract: Mounting of the acute inflammatory response is crucial for host defense and pivotal to the development of chronic inflammation, fibrosis, or abscess formation versus the protective response and the need of the host tissues to return to homeostasis. Within self-limited acute inflammatory exudates, novel families of lipid mediators are identified, named resolvins (Rv), protectins, and maresins, which actively stimulate cardinal signs of resolution, namely, cessation of leukocytic infiltration, counterregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
366
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 443 publications
(373 citation statements)
references
References 140 publications
5
366
0
2
Order By: Relevance
“…As discussed, LTB4 is a neutrophil chemoattractant, but after lipid-mediator class switching pro-inflammatory lipid mediator production pathways are altered to instead produce pro-resolution mediators such as lipoxin A4 (LXA4) 116,117 . Other pro-resolution lipid mediators include resolvins and protectins and stop the influx of new neutrophils 118 .…”
Section: Reverse Migration Of Neutrophilsmentioning
confidence: 99%
“…As discussed, LTB4 is a neutrophil chemoattractant, but after lipid-mediator class switching pro-inflammatory lipid mediator production pathways are altered to instead produce pro-resolution mediators such as lipoxin A4 (LXA4) 116,117 . Other pro-resolution lipid mediators include resolvins and protectins and stop the influx of new neutrophils 118 .…”
Section: Reverse Migration Of Neutrophilsmentioning
confidence: 99%
“…A simplistic view is that n-3 PUFAs form the basis of lipid derivatives with anti-inflammatory properties, whereas n-6 PUFAs are the precursors of proinflammatory mediators, and stimulate the production and activity of proinflammatory factors such as cytokines (Farooqui et al, 2007;Orr et al, 2013;Serhan et al, 2014). As a result, we have previously demonstrated that low dietary intake of n-3 PUFAs promotes neuroinflammatory responses through the regulation of microglial cells activity and polarization toward a pro-inflammatory phenotype, while n-3 PUFA dietary supplementation is rather anti-inflammatory (De SmedtPeyrusse et al, 2008;Mingam et al, 2008;Labrousse et al, 2012;Madore et al, 2014;Delpech et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…SPM are produced via the actions of specific lipoxygenases on different substrates, including arachidonic acid-derived lipoxins (LXA 4 and LXB 4 ), eicosapentaenoic acid (EPA)-derived E-series resolvins (RvE1-3), docosahexaenoic acid (DHA)-derived D-series resolvins (RvD1-6), maresins and protectins (10, 12–24). Activation of resolution signals occurs when specific SPMs interact with cognate G-protein coupled receptors (GPCRs) present on the cell surface (25, 26). Lipoxin A 4 (LXA 4 ) binds its receptor, ALX/FPR2, transducing signals with potent actions in experimentally induced animal disease models (27).…”
Section: Introductionmentioning
confidence: 99%